Model Dukungan Orang Tua terhadap Pendidikan Santri di Pondok Pesantren - Dimas Pahlawanita Damayanti (Qalam : Jurnal Ilmu Kependidikan, 2023)
This research aims to examine the importance of parental support in the Islamic boarding school environment and analyze various support models that can be applied. The research method used is Library Research. The research results show that parental support in Islamic boarding schools has an important role in supporting the development of students. There are several support models that can be applied, including emotional, social, economic and participatory support. Each support model has a specific role in helping students achieve better academic achievement and positive personal development. The impact of parental support on students is very significant. Students who receive adequate support tend to have higher levels of happiness and greater motivation to learn. This support also helps students overcome problems and challenges that may arise during their stay at the Islamic boarding school. Apart from that, open communication between parents and students in Islamic boarding schools plays an important role in creating an environment that supports the holistic development of students. This communication helps parents understand their child’s needs and helps students feel more comfortable in the Islamic boarding school environment. Keywords: Parental support, Islamic boarding school, parental support model.